Coordination compounds and chemical compositions with antioxidant properties - Ion Bulhac; Anastasia Ștefîrță; Lilia Brînză; Eduard Coropceanu; Leonid Voloșciuc; Maria Cocu (Acta et Commentationes Exact and Natural Sciences, 2023)
In the paper there are presented the main results that argue the antioxidant effect of BACC and some chemical compositions on plants. The anti-stress action of the new preparations - Conimid, Difecoden, Fludisec, Polyel, Galmet and Thiogalmet, is provided by increasing the antioxidant protection capacity due to the decrease of the content of malondialdehyde, intensification of the activity of antioxidant enzymes, increase in the content of non-enzymatic antioxidants with low molecular mass. The possibilities of optimizing the resistance of plants to oxidative stress, caused by drought, and stabilization of plant productivity are promising. The biological performance of plants pre-treated with BACC and antioxidant preparations are more fully realized under both optimal moisture and moderate drought conditions.